<---- Sponsored ads ------ >

Solve, 9 + 6x = -x2


Solution.

Given equation is 9 + 6x = -x2

Converting given equation into Standard Form of Quadratic Equation. ax2 + bx + c = 0

9 + 6x = -x2 converted into 2x2 + 6x + 9 = 0

Comparing it with the standard Form of Quadratic Equation ax2 + bx + c = 0

a = 2, b = 6, c = 9

As we know, discriminant = b2 - 4ac

Discriminant = (6)2 - 4(2)(9)

Discriminant = 36 - (72)

Discriminant = -36

Since discriminant < 0
No real root.

<---- Sponsored ads ----- >

© 2020-2030 Amibba Systems Private Limited. All rights reserved.